FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN DIET PADA PASIEN DIABETES MELITUS TIPE 2 DI KECAMATAN SUMBANG BANYUMAS - Ernawati, Dwi Arini; Harini, Ika Murti; Gumilas, Nur Signa Aini (Journal of Bionursing, 2020)
Background problem: Diabetes Mellitus (DM) prevalence in Indonesia based on the results of basic health Research (RISKESDAS) year 2013 is 2.1%, in Central Java  18.33%. Banyumas District has an incidence rate of 1,417 in 2014 and Sumbang Sub-district has the highest incidence rate of DM type 2. Management in DM sufferers is integrated, including eating arrangements, physical activity, education, and medicines. Meal arrangement for patients with type 2 DM includes setting against 3J: number, type and meal schedule in a day. Patients with DM who have already run a diet program has not been able to control blood glucose properly. Food arrangement often fails due to the disobedience of sufferers in running their diet. Many factors affect dietary compliance, among them the level of education, level of knowledge, self-motivation, family support and the role of health workers.Objective: To determine the factors that affect the compliance of diet in diabetes mellitus type 2 patients in Sumbang Sub-district of Banyumas.Methods: The studies used are cross sectional, the level of compliance seen from 3J, i.e. precise amounts, precise types and precise schedules. Samples taken from DM patients who are in Prolanis present during laboratory examination in June 2019. Sampling technique using total sampling. Bound variables are the level of dietary compliance, the free variables are education levels, knowledge levels, self-motivation, family support and the role of health workers.Results: The number of samples was 32 people, who were obedient in a diet of 15 people (46.9%), who did not obey 17 people (53.1%). The P value of the factor variable factors affecting the diet is: age p = 0.411, sex p = 0.035, Job p = 0131, long DM p = 0.261, education level p = 0.035, knowledge level p = 0.036, self motivation p = 0.464, family support p = 0.314, and P Health worker, p = 0.452. Variables that have a meaningful relationship (P < 0.05) with dietary compliance levels are gender, level of education and level of knowledge. As for the variable age, employment, old DM, self-motivation, family support, and the role of health workers have an insignificant relationship (P > 0.05Conclusion: From 32 patients DM most have a level of diet compliance in the category of disobedient 17 people (53.1%), there is a meaningful relationship between gender, education level and level of knowledge with DM dietary compliance,